The Impact of Financial Globalization on Financial Development in Nigeria (1981 – 2021) - Okoduwa, Dorothy Ivie (The Journal of Accounting and Management, 2024)
Financial globalization has been predicted to facilitates capital inflows and enhance the internationalization of financial services. Despite various financial liberalization policies, the performance of the Nigerian financial sector has been unimpressive. This study analyzed the impact of financial globalization on financial development in Nigeria. The study covered the period 1981 to 2021 and employed the Auto-regressive Distributed lag (ARDL) technique. The result from the study showed that financial globalization significantly enhanced financial development (proxied by banking sector development and enhanced stock market development). Thus, the study concluded that financial globalization is a significant driver of both banking sector development and stock market development. The study recommended the need for more active financial globalization reforms that can enhance the growth of the banking sector and the stock market.